LOGISTICS MANAGEMENT OF LAND PACKAGE COMPANIES IN CIUDAD DEL ESTE - Irala Olazar, Luciana; Beatriz Benítez de Amarilla, Silvia (Revista Gênero e Interdisciplinaridade, 2024)
The main purpose of this study was to analyze the current situation and logistics management of parcel distribution companies in Ciudad del Este during the 2022 school year. The methodology used qualitative descriptive research has been used, which has served to develop the most important aspects of this work, from the approach to the contracting of the results obtained in the interview conducted. The interview technique was applied in a population of 10 companies located in Ciudad del Este, of which 3 companies were taken for the application of the research, the surveys were directed to the managers and officials in charge of logistics management. The research work consists of four units. Unit 1: Logistics planning system. Unit 2: Distribution logistics. Unit 3: Distribution planning. Unit 4: Quality control. The findings indicated that the different units of the logistics process such as: inventory management, load distribution and transport managers, information flow and order processing, storage and distribution have a favorable influence on the logistics management of the companies studied. Based on the results in all companies, in order to achieve competitive advantages, a comprehensive logistics system is necessary that allows all processes to be carried out in an orderly and efficient manner, thus reducing costs, organizing processes, exercising control and improving each of the company’s areas. With the constant improvement of transport, and the correct distribution of materials in the construction process, it will be more efficient and this will lead to a reduction in direct and indirect costs.